Al-Ghazali and Buya Hamka's thoughts on Islamic education - Naili Hidayati; Syamsul Aripin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study compares the thoughts of Imam Al-Ghazali and Buya Hamka on Islamic education. Both are key figures who have profoundly influenced the development of Islamic education. This paper examines their views on the goals of education, curriculum design, the role of teachers in the learning process, and how religion shapes students' character. Despite living in different eras, their ideas remain relevant in efforts to improve the quality of Islamic education in the modern era.